2012 Information and Communications for Development : Maximizing Mobile - World Bank (Washington, DC: World Bank, 2012)
With some 6 billion mobile subscriptions in use worldwide, around three-quarters of the world's inhabitants now have access to a mobile phone. Mobiles are arguably the most ubiquitous modern technology: in some developing countries, more people have access to a mobile phone than to a bank account, electricity, or even clean water. Mobile communications now offer major opportunities to advance human development from providing basic access to education or health information to making cash payments to stimulating citizen involvement in democratic processes. The developing world is 'more mobile' than the developed world. In the developed world, mobile communications have added value to legacy communication systems and have supplemented and expanded existing information flows. However, the developing world is following a different, 'mobile first' development trajectory. Many mobile innovations such as multi-SIM card phones, low-value recharges, and mobile payments have originated in poorer countries and are spreading from there. New mobile applications that are designed locally and rooted in the realities of the developing world will be much better suited to addressing development challenges than applications transplanted from elsewhere. In particular, locally developed applications can address developing-country concerns such as digital literacy and affordability. This 2012 edition of the World Bank's information and communications for development report analyzes the growth and evolution of mobile telephony, and the rise of data-based services delivered to handheld devices, including apps. The report explores the consequences for development of the emerging 'app economy.' It summarizes current thinking and seeks to inform the debate on the use of mobile phones for development. This report looks at key ecosystem-based applications in agriculture, health, financial services, employment, and government, with chapters devoted to each.